1982
DOI: 10.1111/j.1469-8137.1982.tb03411.x
|View full text |Cite
|
Sign up to set email alerts
|

ACCUMULATION OF CALCIUM OXALATE IN THE MANTLE OF ECTOMYCORRHIZAL ROOTS OF PINUS RADIATA AND EUCALYPTUS MARGINATA

Abstract: SUMMARYCalcium oxalate crystals occur in the mantle of ectotnycorrhizal roots of Pinus radiata and Eucalyptus marginata. Dense concentrations of these crystals were observed in association with the fungal symbiont of both tree species. It is suggested that oxalate production may enhance nutrient uptake by ectomycorrhizal roots of forest species gromng in nutrient impoverished soils. Concentrations of Ca^ S^ K and P were similar in mycorrhizal root masses of P. radiata and ii. marginata.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
7

Year Published

1984
1984
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(39 citation statements)
references
References 14 publications
1
31
0
7
Order By: Relevance
“…Although the preservation of these older root nodules does not provide visual evidence of mycorrhizal fungi, the presence of calcium in only the root nodules offers some chemical evidence that fungi were once there. In extant plants, mycorrhizal fungi often contain a large amount of calcium oxalate, which is used to break down soil into usable minerals (4,29).…”
Section: Discussionmentioning
confidence: 99%
“…Although the preservation of these older root nodules does not provide visual evidence of mycorrhizal fungi, the presence of calcium in only the root nodules offers some chemical evidence that fungi were once there. In extant plants, mycorrhizal fungi often contain a large amount of calcium oxalate, which is used to break down soil into usable minerals (4,29).…”
Section: Discussionmentioning
confidence: 99%
“…These deposits varied in size and number and, although there was some variation in distribution, most of them occurred either at the mantle surface or among loosely organized outer mantle hyphae. Crystals have been noted previously in ectomycorrhizas formed by Rhizopogon species and the closely related genus Suillus with several genera of Pinaceae (Malajczuk & Cromack, 1982 ;Agerer, 1990 ;Treu, 1990 ;Massicotte et al, 1992Massicotte et al, , 1994Agerer et al, 1996) and it has been suggested that these deposits might be partially responsible for the various colours displayed by fungal mantles (Massicotte et al, 1994). It is possible that these deposits are of calcium oxalate, a common extracellular substance localized along hyphae of many fungal species (O'Connell et al, 1983 ;Whitney & Arnott, 1987).…”
Section: mentioning
confidence: 99%
“…If, in addition to their large surface area mycorrhizas are associated with chemical activity, the significance for nutrient cycling is immense. There are reports of exudation of organic acids by fungi and mycorrhizas (Graustein, Cromack & Sollins, 1977;Malajczuk & Cromack, 1982;Jurinak et al, 1986), of the accumulation of phosphorus as polyphosphate by mycorrhizas ) and of increased phosphatase activity at the mycorrhizal surface (although the latter are rather variable -see Antibus et al, 1981;Dighton, 1983 ;Dodd et al, 1987). The further definition of this potentially active role of mycorrhizas in forests, particularly where mycorrhizas are concentrated as a root mat or in the litter layers, seems to us to be a high research priority (and see also Hetrick, 1989;Bolan, 1991).…”
Section: Nutrientsmentioning
confidence: 99%